1985
DOI: 10.1161/01.atv.5.6.613
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of low density lipoprotein by plasmapheresis in familial hypercholesterolemia.

Abstract: Plasma lipoproteins were selectively removed from familial hypercholesterolemic patients by using two types of plasmapheresis: double-membrane filtration and selective adsorption of very low density lipoproteins (VLDL) and low density lipoproteins (LDL). In both techniques, plasma was separated from blood cells by using hollowfiber filters, and 100% of the VLDL and LDL was recovered in the filtrate. In doublemembrane filtration, the second hollow-fiber filter trapped 84% of LDL + VLDL, 48% of high density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(93 citation statements)
references
References 23 publications
2
90
0
1
Order By: Relevance
“…Some studies have reported that LDL apheresis therapy was safe in children without influencing development/growth, and that this therapy led to the reduction/disappearance of skin xanthoma, inhibiting exacerbation of aortic valve stenosis/supravalvular stenosis, which are characteristic of homozygous FH, and coronary lesions, or resulting in improvement [73][74][75][76][77][78][79][80] . Irondeficiency anemia is the most frequent side effect.…”
Section: Effects Of Ldl Apheresismentioning
confidence: 99%
“…Some studies have reported that LDL apheresis therapy was safe in children without influencing development/growth, and that this therapy led to the reduction/disappearance of skin xanthoma, inhibiting exacerbation of aortic valve stenosis/supravalvular stenosis, which are characteristic of homozygous FH, and coronary lesions, or resulting in improvement [73][74][75][76][77][78][79][80] . Irondeficiency anemia is the most frequent side effect.…”
Section: Effects Of Ldl Apheresismentioning
confidence: 99%
“…3 LDL apheresis is efficacious in lowering plasma cholesterol, but its effect is transient and treatment has to be repeated every 2 to 3 weeks. 4,5 The lack of an effective treatment for FH prompted the exploration of gene therapy as an alternative approach to the management of this devastating disease.…”
Section: Introductionmentioning
confidence: 99%
“…The latter has been shown to reduce mortality of CAD [64]. New tech niques have been developed to replace plasmaphere sis, which selectively remove apolipoprotein-B-► containing lipoproteins from plasma [65][66][67][68][69]. The performance of regular LDL-apheresis permits the achievement of lower levels of LDL-cholesterol, which are usually not possible to attain with drug therapy alone [70][71][72][73].…”
Section: Ldl-apheresismentioning
confidence: 99%